Relationship between knowledge, practice of mental training skill, control and confidence among Malaysian sport school students - Surat, Shahlan; Mustafa, Nurhani Munawwarah; Ramli, Shalinawati; Baharudin, Harun; Mohamad Yusop, Yusni; Zainudin, Zaida Nor (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: The objective of the study is to identify the relationship between knowledge and the practice of mental training skill during competitions which requires the athletes to gain control and boost their confidence. The study significantly states that knowledge and the practice of mental training skill during competitions are able to increase the athletes’ ability to control their state of mind and raise their confidence. Methods: 115 students of Malaysian Sport School, Pahang Malaysia participated in the study. One set of Likert scale questionnaire, which consists of five parts is used as the study instrument. The study instrument is based on the Competitive State Anxiety Inventory (CSAI-2), Test of Performance Strategies (TOPS) and Mental Toughness Questionnaire (MTQ-48). Results: The research findings demonstrate an average level of knowledge on mental training skill with reference to the athletes’ control of their mental state and their confidence. However, the significant relationship between the knowledge and the practice of mental training skill with regards to the athletes’ mind control and confidence during competitions shows a highly positive and moderate relationship. Conclusion: Healthy mental training skill helps improve the athletes’ personality during competition. Apart from prioritising on the physical element in training applied in the competitions, the main elements which become the athletes’ source of mental strength, level of control and confidence are able to overcome the mental challenges.